Optical Imaging, Photodynamic Therapy and Optically Triggered Combination Treatments. Issue 3 (May 2015) - Mallidi, Srivalleesha; Spring, Bryan Q.; Chang, Sung; Vakoc, Benjamin; Hasan, Tayyaba
Abstract : Abstract: Optical imaging is becoming increasingly promising for real-time image-guided resections, and combined with photodynamic therapy (PDT), a photochemistry-based treatment modality, optical approaches can be intrinsically "theranostic." Challenges in PDT include precise light delivery, dosimetry, and photosensitizer tumor localization to establish tumor selectivity, and like all other modalities, incomplete treatment and subsequent activation of molecular escape pathways are often attributable to tumor heterogeneity. Key advances in molecular imaging, target-activatable photosensitizers, and optically active nanoparticles that provide both cytotoxicity and a drug release mechanism have opened exciting avenues to meet these challenges. The focus of the review is optical imaging in the context of PDT, but the general principles presented are applicable to many of the conventional approaches to cancer management. We highlight the role of optical imaging in providing structural, functional, and molecular information regarding photodynamic mechanisms of action, thereby advancing PDT and PDT-based combination therapies of cancer. These advances represent a PDT renaissance with increasing applications of clinical PDT as a frontline cancer therapy working in concert with fluorescence-guided surgery, chemotherapy, and radiation.